Management of Facilities and Infrastructure at the Office of the Regional Technical Implementation Unit for the Protection of Women and Children of East Luwu Regency - Karina, Elma; Nasrullah, Muh; Isgunandar (Pendidikan Administrasi Perkantoran, UNM, 2025)
Facilities and infrastructure play an important role in an agency or organization. Office facilities and infrastructure are facilities needed to support the smooth operation of an office or an activity or activity. Facilities are direct equipment used to achieve targets or goals, while infrastructure is a facility that acts as a supporting structure for the process of achieving targets and objectives of the agency. Therefore, it is important to manage facilities and infrastructure with careful consideration. This study aims to determine the management of facilities and infrastructure at the UPTD PPA (Women and Children Protection) office of East Luwu Regency. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The findings show that: (1) Planning and determination of needs in the management of facilities and infrastructure has been carried out according to procedures such as identifying needs, the arrangement of budget plans and their implementation remain under monitoring. (2) The procurement budgeting for UPTD runs according to the procedure, but the implementation is not optimal due to constraints in planning revision (3) The procurement process has not fully run optimally because the process takes about 1 year. (4) The storage of office equipment has been running well, with supervision through the SIMDA application and regular checking. The distribution of office equipment, which takes about 6 months, is not fully optimal. (5) The maintenance of facilities and infrastructure at the UPTD office has been running well through routine maintenance and repairs in case of damage. (6) At the UPTD office, the deletion has not been running optimally because the office is still newly formed, and the temporary deletion team is also not official. (7) Control and Inventory are quite good with the SIMDA – BMD system, but it still has weaknesses in physical supervision due to the absence of CCTV. In general, the management of facilities and infrastructure at UPTD PPA has been running quite well although it still requires increased coordination and optimization.